2019
DOI: 10.2147/opth.s182751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Wide-angled endoillumination vs traditional scleral buckling surgery for retinal detachment &ndash; a comparative study</p>

Abstract: PurposeTo evaluate the surgical outcomes of traditional scleral buckling (TSB) compared to chandelier-assisted scleral buckling (CSB) for rhegmatogenous retinal detachment repair.Patients and methodsA retrospective interventional comparative case series of 49 eyes that underwent SB procedure. Medical records of 27 and 22 eyes that underwent TSB and CSB surgery, respectively, were evaluated. Outcome measures included primary anatomical success, visual acuity (VA), and perioperative complications.ResultsPrimary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
5
19
0
Order By: Relevance
“…Several studies have reported that the use of chandelier-assisted scleral buckling yielded a reattachment rate of 83.3–95.5% without any significant intraoperative and postoperative complications 311. In our current study, reattachment was achieved in all of the 18 cases after the first scleral buckling.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have reported that the use of chandelier-assisted scleral buckling yielded a reattachment rate of 83.3–95.5% without any significant intraoperative and postoperative complications 311. In our current study, reattachment was achieved in all of the 18 cases after the first scleral buckling.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, Frisina et al reported 213 eyes of primary RRD who underwent microscope-assisted ab externo surgery and demonstrated the safety and efficacy of this technique [ 15 ]. However, the reported studies on chandelier endoillumination-assisted scleral buckling cover a limited follow-up period, ranging from 1 to 12 months [ 3 , 16 21 ]. Our group applied 25-gauge cannula-based chandelier-assisted scleral buckling since 2013.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter study also confirmed that patients with phakic moderately complex primary RRD who underwent scleral buckling had significantly better visual outcomes [ 10 ]. Several studies have reported that the use of chandelier-assisted scleral buckling yielded a reattachment rate of 83.3-95.5% [ 3 , 5 ]. The primary anatomical success rate in our study was 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a trocar canula was an elegant approach which provided easy access for the chandelier light with minimal trauma to the sclera or vitreous. The efficacy and safety of this procedure has been reproduced in reports of successful scleral buckling using chandelier illumination [ 6 9 ]. Decreased case duration, improved primary reattachment rate and visual acuity, and augmented educational value of the chandelier assisted scleral buckle was reported by Narayanan et al in 2016 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%